Georg Benjamin Mendelssohn 1794-1874 - Hohmann, Joseph (ERDKUNDE, 1969)
On 16. November 1969 the Bonn Geographical Institutes commemorate the 175th birthday of Georg Benjamin Mendelssohn, who was the first ,professional geographer’ (Philippson) to gain his ,Habilitation’ distinction at the University of Bonn. G. B. Mendelssohn, grandson of the philosopher Moses Mendelssohn, was born on 16. November 1794 in Berlin and gained his doctorate in Kiel with a thesis entitled: Observationes geologico-geographicae de naturalibus soli in Germania formis. He gained his ’Habitation’ in 1828 in Bonn, was awarded a personal professorhip in 1835 and became full Professor of Geography and Statistics in 1847. In 1836 Mendelssohn published his mayor work Germanic Europe’, which clearly shows the influence of Carl Ritter and which entitles its author to a place among the classical geographers. Mendelssohn’s manysided personality was distinguished by literary and political interests. He died on 24. August 1874 at his country home at Horchheim near Koblenz.